Service Quality for Banjarbendo Village Government - Hary Putra Wibowo; Lailul Mursyidah (Indonesian Journal of Public Policy Review, 2022)
The Village Government is one part of the state administrators who have the task of providing good quality public services to the community based on five indicators of public services, namely tangible, reliability, responsiveness, assurance and empathy. The analysis technique in this study uses the service quality (Servqual) technique or a technique that produces a gap score derived from the results of service performance to the community with the expectation of service quality expected by the community. The results of this study indicate that the quality of administrative services for the Banjarbendo Village Government, Sidoarjo District, Sidoarjo Regency can be categorized as poor administrative service quality because it produces an overall average gap score (-0.3400) and a gap score on the five dimensions 1) Physical Evidence/ Tangible (-0,13809) with bad category, 2) Reliability (-0.3728) with bad category, 3) Responsiveness (-0.3356) with bad category, 4) Assurance (-0.3587) with bad category, and 5) Caring/Empathy (-0.2548) with bad category.